Intervensi Non Farmakologis untuk Memperbaiki Status Fungsional Pasien Kanker dengan Chemotherapy-Induced Peripheral Neuropathy (CIPN) - Handriani, Hani; Afiyati, Yati; Allenidekania, Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify non-pharmacological interventions that can improve the functional status of cancer patients with chemotherapy-induced peripheral neuropathy (CIPN). The research method uses a systematic review through literature searches from 4 databases: SAGE, PUBMED, SCIENCE DIRECT, and PROQUEST. The research results show that from 12 research articles, non-pharmacological interventions to improve functional status in CIPN can be grouped into physical and non-physical interventions. Physical interventions include physical exercise and stimulation, while non-physical interventions are through self-management. In conclusion, physical intervention effectively reduces the pain scale and sensory symptoms of CIPN, which improves the patient's functional status and quality of life. However, in some literature, it is stated that a combination with pharmacological therapy can reduce CIPN complaints. Keywords: CIPN, Non-Pharmacological Intervention, Functional Status